KEMAMPUAN STRUKTUR FINANSIAL, PERTUMBUHAN NASABAH, DAN LOAN TO DEPOSIT RATIO SEBAGAI PREDIKTOR RENTABILITAS LEMBAGA PERKREDITAN DESA - Putra, I Dewa Gede Adhita Tisna; Suardikha, I Made Sadha (E-Jurnal Akuntansi, 2016)
This study aims to determine the effect of the financial structure, customer growth, and loan to deposit ratio to profitability through ROA and BOPO as well as knowing the difference ROA and BOPO ratios in the measurement of profitability. This study chose research sites in the Lembaga Perkreditan Desa Empowerment Institution (LP LPD) Tabanan with the observation period for the years of 2011-2013. The number of samples taken 150 LPD on each Desa Pakraman spread over 10 districts, with a proportionate stratified random sampling method, and retrieval techniques randomly via lottery. Data collected through interviews and observations. The analysis technique used is multiple linear regression and test different. Based on the results of the analysis showed that the results of the t test or the test of the hypothesis model 1, obtained financial structure, customer growth, and Loan to Deposit Ratio effect on profitability with ROA ratio measurement, For t test or the results of hypothesis testing model 2, obtained financial structure, customer growth , and Loan to Deposit Ratio effect on profitability with ROA ratio measurement. For different test results, there are differences between ROA profitability measurement with BOPO ratio and ROA ratio has a value higher measurement accuracy.
Keywords: financial structure, customer growth, loan to deposit ratio, profitability, ROA ratios, BOPO ratios